Limitations in the Interpretation of Intravenous Carotid Digital Subtraction Angiography - Hoffman, Michael G.; Gomes, Antoinette S.; Pais, S. Osher (American Journal of Neuroradiology, 1983)
To evaluate the limitations of intravenous carotid digital subtraction angiography (DSA) in the diagnosis of carotid disease, studies of 130 patients were reviewed. Factors that resulted in a nondiagnostic study included: (1) misregistration larynx artifact overlying the carotid bifurcation; (2) external carotid or vertebral artery overlying the internal carotid artery; and (3) poor arterial contrast density secondary to poor cardiac function. As a result of these limitations, the ideal of adequate demonstration of both carotid bifurcations in two opposite oblique projections or an oblique and anteroposterior projection was achieved in only 34 patients (26%). Of 126 carotid bifurcations that were seen adequately in two or more different projections, 19 (15%) showed an abnormality in one projection but appeared normal in another. These abnormalities would not have been detected had the vessel been visualized only in the spuriously normal-appearing projection. These and other limitations of intravenous DSA, such as contrast load and morbidity, are discussed.